Rectal misoprostol in management of retained placenta: a contradictory result. - Saipin Pongsatha (2018)
Retained placenta is one of the common problems in obstetric practice. The most common procedure to manage cases with retained placenta is manual removal of placenta (MROP) under general anesthesia. Recent data indicates that misoprostol may be helpful in decreasing the rate of MROP. To assess the efficacy of rectal misoprostol in women with delayed placental separation. A descriptive, retrospective cohort was conducted. All pregnant women with retained placenta longer than 30 minutes after fetal delivery, either in second or third trimester that received 800 mcg rectal misoprostol were included in the present study. Successful treatment was defined as spontaneous placental expulsion within 30 minutes after rectal misoprostol administration. The rate of spontaneous placental expulsion within 30 minutes after misoprostol administration was very low, only three out of 20 cases (15%). High dose rectal misoprostol does not give a promising result in cases of retained placenta. It is ineffective to facilitate placental separation in cases of retained placenta and does not seem to decrease the rate of MROP.